2012
DOI: 10.4236/ojsst.2012.21004
|View full text |Cite
|
Sign up to set email alerts
|

Managing Well-Being at Work during 2010s—Expert Viewpoints

Abstract: Current working life is turbulent making maintaining well-being at work challenging. This turbulence necessitates working organisations and their managers to be more sensitive and agile. Managers must understand the human role in technical and organisational systems. The aim of this research is to come up with a description of aspects that influence well-being at work that will be applicable for different types of work places. The research is conducted by interviewing experts, currently working as researchers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Many published citations to the concept of work system, the work system framework, WSLC, and WSM revealed contributions to a researcher's thinking. The following examples date from 2006 to 2012: Benbasat and Zmud (2006), Cuellar, McLean, and Johnson (2006), Curtin, Kauffman, and Riggins (2006), Davamanirajan, Kauffman, Kriebel, and Mukhopadhyay (2006), Gray (2006), Møller (2006), BenMoussa (2007, Goodhue (2007), Kurpjuweit and Winter (2007), Sewchurran and Petkov (2007), Davison, Ou, Li, Martinsons, and Bjorksten (2008), Kosaka (2008), Lyytinen and Newman (2008), Petkov and Petkova (2008), Petersson (2008), Singh and Woo (2008), Beekhuyzen (2009), Gericke and Winter (2009), Gregory and Descubes (2011), Kosaka (2009), Lafaye (2009), Madsen and Vigden (2009), Misra, Petkov, and Petkova (2009), Mettler (2009), Ou and Banerjee (2009), Pinhanez (2009), Ralph and Wand (2009), BenMoussa 2010 2012, Sinisammal, Belt, Härkönen, Möttönen, and Väyrynen (2012). While an increasing number of citations have appeared, the extent to which WST and its applications and extensions will prove useful in IS research is not yet fully evident because of the lengthy time lags in diffusion of new ideas, use of those ideas in research, and eventual publication.…”
Section: Usage In Researchmentioning
confidence: 99%
“…Many published citations to the concept of work system, the work system framework, WSLC, and WSM revealed contributions to a researcher's thinking. The following examples date from 2006 to 2012: Benbasat and Zmud (2006), Cuellar, McLean, and Johnson (2006), Curtin, Kauffman, and Riggins (2006), Davamanirajan, Kauffman, Kriebel, and Mukhopadhyay (2006), Gray (2006), Møller (2006), BenMoussa (2007, Goodhue (2007), Kurpjuweit and Winter (2007), Sewchurran and Petkov (2007), Davison, Ou, Li, Martinsons, and Bjorksten (2008), Kosaka (2008), Lyytinen and Newman (2008), Petkov and Petkova (2008), Petersson (2008), Singh and Woo (2008), Beekhuyzen (2009), Gericke and Winter (2009), Gregory and Descubes (2011), Kosaka (2009), Lafaye (2009), Madsen and Vigden (2009), Misra, Petkov, and Petkova (2009), Mettler (2009), Ou and Banerjee (2009), Pinhanez (2009), Ralph and Wand (2009), BenMoussa 2010 2012, Sinisammal, Belt, Härkönen, Möttönen, and Väyrynen (2012). While an increasing number of citations have appeared, the extent to which WST and its applications and extensions will prove useful in IS research is not yet fully evident because of the lengthy time lags in diffusion of new ideas, use of those ideas in research, and eventual publication.…”
Section: Usage In Researchmentioning
confidence: 99%
“…By way of interviews with researchers, consultants and managers who work for public and private organizations, a study conducted in Finland by Sinisammal et al (2012) identified factors that influence occupational wellbeing. The content of the interviews resulted in five categories: employee (need for self-realization, equilibrium between work and private life, and health promotion), work (possibilities of self-development, significance of the work), group work (companionship, teamwork, positive attitudes in relation to diversity, mutual trust), management (clear practices and rules; communication and transparency; and managerial abilities), and external factors (macro-issues such as the local and global economy; laws; and microissues such as family, friends, personal relations and leisure time).…”
Section: Theoretical Framework 21 Well-being In the Workplacementioning
confidence: 99%
“…Administrating them has become the greatest challenge for managers that seek to create value, satisfaction and necessary conditions for the good performance of their employees, identifying effective strategies for promoting well-being in the workplace. Sinisammal, Belt, Härkönen, Möttönen, and Väyrynen (2012) affirmed that the benefits of well-being at work are extendable to employees, employers and the national economy. In the case of organizations, an appropriate level of well-being would increase quality and productivity, as well as positively influence the reduction of health problems that lead to sick leave.…”
Section: Introductionmentioning
confidence: 99%
“…However, agri-food facilities must ensure not only the consumers' hygiene safety, by adopting all the precautions and building solutions which may guarantee adequate safety levels for product contamination, but also an adequate safety level for workers (Sinisammal et al, 2012). Recently, EU-27 has implemented the European 2007-2012 strategy on health and safety at work (European Commission, 2007) establishing six intermediate objectives in order to achieve a 25% reduction in the total incidence rate of accidents at work.…”
Section: Introductionmentioning
confidence: 99%